Cells from subcutaneous tissues contribute to scarless skin regeneration in Xenopus laevis froglets. Issue 8 (15th June 2017) - Otsuka‐Yamaguchi, Rina; Kawasumi‐Kita, Aiko; Kudo, Nanako; Izutsu, Yumi; Tamura, Koji; Yokoyama, Hitoshi
Abstract : Background : Mammals cannot regenerate the dermis and other skin structures after an injury and instead form a scar. However, a Xenopus laevis froglet can regenerate scarless skin, including the dermis and secretion glands, on the limbs and trunk after skin excision. Subcutaneous tissues in the limbs and trunk consist mostly of muscles. Although subcutaneous tissues beneath a skin injury appear disorganized, the cellular contribution of these underlying tissues to skin regeneration remains unclear.Results : We crossed the inbred J strain with a green fluorescent protein (GFP)‐labeled transgenic Xenopus line to obtain chimeric froglets that have GFP‐negative skin and GFP‐labeled subcutaneous tissues and are not affected by immune rejection after metamorphosis. We found that GFP‐positive cells from subcutaneous tissues contributed to regenerating the skin, especially the dermis, after an excision injury. We also showed that the skin on the head, which is over bone rather than muscle, can also completely regenerate skin structures.Conclusions : Cells derived from subcutaneous tissues, at least in the trunk region, contribute to and may be essential for skin regeneration. Characterizing the subcutaneous tissue–derived cells that contribute to skin regeneration in amphibians may lead to the induction of cells that can regenerate complete skin structures without scarring in mammals. Developmental Dynamics 246:585–597, 2017 . © 2017 Wiley Periodicals, Inc. Key Findings: The Xenopus froglet can regenerate scarless skin on the head, limb, and trunk after an excision skin wound. Using the inbred J strain with a GFP‐labeled transgenic Xenopus line allows chimeric analysis of cell fate without immune rejection, even after metamorphosis. Cells from subcutaneous tissues help regenerate the dermal layer after a whole‐thickness skin injury in the Xenopus froglet.